Anterior haptic flexing and in‐the‐bag subluxation of an accommodating intraocular lens due to excessive capsular bag contraction. Issue 9 (September 2015) - Kramer, Gregory D.; Werner, Liliana; Neuhann, Tobias; Tetz, Manfred; Mamalis, Nick
Abstract : N/A: We describe the case of a patient who had cataract surgery with implantation of the hydrophilic acrylic Tetraflex accommodating intraocular lens (IOL), with subsequent development of capsulorhexis phimosis and in‐the‐bag IOL subluxation. Contraction of the capsular bag secondary to fibrosis resulted in significant anterior flexing of the lens haptic component. Explantation of the IOL–capsular bag complex was required 7 years after implantation. Histopathologic analysis demonstrated multiple areas of thick anterior subcapsular fibrosis. Pseudoexfoliative material was present throughout the surface of the lens capsule. Intraocular lenses manufactured from hydrophilic acrylic material are highly flexible and may be more susceptible to capsule contraction, even in the absence of predisposing ocular and systemic conditions. This case highlights the importance of developing guidelines regarding patient screening and selection for the appropriate use of accommodating and other highly flexible IOLs. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.